High-performance ternary π-conjugated copolymers containing diarylethylene units: synthesis, properties, and study of substituent effects on molecular aggregation and charge transport characteristics. Issue 2 (14th December 2018) - Wei, Congyuan; Zhang, Weifeng; Zhou, Yankai; Huang, Jianyao; Li, Dizao; Wang, Qiang; Yu, Gui
Abstract : High-performance ternary π-conjugated copolymers containing diarylethylene units were designed and synthesized. Abstract : We report the design and synthesis of a series of ternary π-conjugated copolymers, namelyPDST, PDSTF, andPDSTCN, in which diarylethylene and diketopyrrolopyrrole units are conjugated alternately. ForPDSTF andPDSTCN, fluorine atoms and cyano units are introduced in the molecular backbone to fine-tune the molecular conformation and packing mode. The optical, electrochemical, and thermal properties, molecular structures, etc. of the three copolymers were fully investigated by experimental methods and theoretical simulations, respectively. Besides, their charge transport properties were explored by fabricating polymer field-effect transistors (PFETs) with a bottom-gate/bottom-contact configuration. All these ternary copolymer-based PFETs showed typical p-channel charge transport characteristics under ambient conditions. The highest hole mobility obtained is 1.26 cm 2 V −1 s −1 forPDST, 2.20 cm 2 V −1 s −1 forPDSTF, and 1.18 cm 2 V −1 s −1 forPDSTCN . In addition, we studied the substituent effect on molecular aggregation, revealing that incorporating fluorine atoms into the ternary π-conjugated copolymers is beneficial for obtaining highly-ordered, edge-on lamellar packing molecular aggregation, and further leads to improved charge mobility, whereas the introduction of cyano groups induces an opposite effect.